Menu Profitability Optimization Strategy Using Menu Engineering at Cafe Cali Jakarta - Serafine Nadia Agnesia; Antonius Rizki Krisnadi (Darul Yasin Al Sys, 2026)
Cafe Cali Jakarta is a luxury rooftop bar operating under The Orient Jakarta in the premium Sudirman district of Central Jakarta; therefore, strategic menu portfolio management is essential for sustaining profitability amid high operational overhead and increasingly competitive rooftop venue dynamics. This study aims to analyze the popularity performance and contribution margin of each menu item, classify the items within the Menu Engineering matrix, and formulate data-driven menu optimization strategies. This study employed a descriptive quantitative approach supported by qualitative analysis. Sales data from January to October 2025, covering 36 active menu items across eight categories, were analyzed using the Menu Engineering method developed by Kasavana and Smith (1982). Qualitative data were collected through in-depth interviews with Dian Nugraha Firdaus as the key informant, Rangga Oktafidiawan as the main informant, and Evelina Kusumawardhani as an additional informant, supported by field observation for data triangulation. The findings indicate that, of the 36 menu items analyzed, 12 items (33.3%) were classified as Stars, 13 items (36.1%) as Plow Horses, seven items (19.4%) as Puzzles, and four items (11.1%) as Dogs. The Stars quadrant contributed 43.5% of the total portfolio contribution margin, indicating its central role in supporting menu profitability. Based on this classification, the recommended strategies include maintaining the quality of Stars while applying incremental price increases, improving Plow Horses margins through bundling and gradual repricing, increasing Puzzles visibility through structured suggestive selling and social media campaigns, and conducting contextual per-item evaluations for Dogs using a substitution-first approach. This study concludes that Menu Engineering provides a practical analytical basis for optimizing menu profitability and strategic decision-making in premium food and beverage venues. Its contribution lies in integrating quantitative menu performance analysis with qualitative managerial insights to support evidence-based menu optimization in a competitive rooftop bar context.